1984: The Australasian Fifth Annual Study Skills Conference: Language and Learning at Tertiary Level - Meyer (Convenor), Rosalind (Journal of Academic Language and Learning, 2026)
Formatting notes: In the pdf, individual articles can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. The proceedings have no consistent pagination on the print pages. Indicated page numbers are the page number of the pdf file. ’By Indirections Find Directions Out’: Introduction to University Study: B. Ballard, J. Clanchy, and J. Taffe … 9 Survey Results: Douglas Bate … 21 ’Improving Access to Tertiary Education’: Vic Beasley … 60 ’Bridging the Gaps – Study Support Services for Off-Campus Students at the University of New England’: D. Bowlay and S. Dorland … 69 ’The Sentence is Basic’: Helen Drury … 82 Teaching Before Learning or Learning Before Teaching? Nerida F. Ellerton … 93 ’Some Aspects of Body Movement in Communication’: June Gassin … 100 ’Communicating Mathematical Skills and Ideas in Tertiary Institutions’: Joe Gilks … 102 ’Developing Audio Learning Skills Materials for External Students’: Lorraine Marshall … 107 ’Analysis and Synthesis: Developing Report Writing Skills in Tertiary Students’: M. Rosanna McEvedy … 109 ’Easing the Entry’ A Study Skills Programme for New Mature Entrants: Neil Quintrell … 132 Let’s Use the Video-Computer Link: Gloria E. Robbins and Sandy M. Pottinger … 150 ’Industrialised, Individualised or Independent?’: Frances Rowland … 155 Interactive Video and Foreign Language Learning in the 80’s: Liz Temple … 189 Eloquence & Literacy: Peter J. Wakeham … 197 Improving Students’ Essays: Carolyn Webb … 208 Developing Postgraduate Research Skills: Ortrun D. Zuber-Skerritt … 225 Head Counting or Skull-Duggery: A Case of Caput Mortuum? Hanne Bock And Helene Lewit … 229 Generic Structures and Learning to Write: Frances Christie … 242 Purifying the Tribal Language: What Do They Know of English, Who Only English Know? Emiritus Professor C.E. Moorhouse … 263 Cognitive Differences in Processing of Words and Pictures: A Cross Cultural Comparison: Barry L. Richardson and Dianne B. Wuillemin … 284 Reading as Interpretation: The Jefferson Scandal: Gordon Taylor … 297 Age of Acquisition: A Determinant of Hemispheric Dominance for Language Processing in Papua New Guineans: Dianne Wuillemin … 316 Developing Post Graduate Research Skills: 0. Zuber-Skerritt and A. Rix … 326 Report on a Workshop: On ’Developing Postgraduate Research Skills’ … 348